Measuring Tax-Sensitive Institutional Investor Ownership - Blouin, Jennifer L.; Bushee, Brian J.; Sikes, Stephanie A. (The Accounting Review, 2017)
ABSTRACT We classify all institutional investors that file Form 13-F over the period 1995–2013 as either “tax-sensitive” or “tax-insensitive” based on their trading behavior and portfolio characteristics. We examine tests of the effects of investor tax-sensitivity on portfolio rebalancing, price pressure, and fund performance, and compare our measure of tax-sensitive institutional investor ownership to three measures used in prior studies. We show that our measure of tax-sensitive investors dominates other measures in the portfolio rebalancing and price pressure tests. In the fund performance test, our measure of tax-sensitivity is the only one that finds that tax-sensitive investors have significantly lower returns on their portfolio stocks, which is a new result in the literature. JEL Classifications: G11; G20; H24.